2015
DOI: 10.1093/femsle/fnv053
|View full text |Cite
|
Sign up to set email alerts
|

Inefficient translocation of a truncated O unit by a Salmonella Wzx affects both O-antigen production and cell growth

Abstract: Bacterial Wzx flippases translocate (flip) short oligosaccharide repeat units (O units) across the inner membrane into the periplasm, which is a critical step in the assembly of many O antigens, capsules and other surface polysaccharides. There is enormous diversity in O antigens and capsules in particular, even within species. Wzx proteins are similarly diverse, but it has been widely accepted that they have significant specificity only for the first sugar of an O unit. In this study, we analysed the Wzx from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…The loss of WzxB causes the accumulation of Und-PPlinked O-antigen intermediates (49), which in turn limits the availability of Und-P for PG synthesis. Because of this, wzxB mutants are notoriously difficult to isolate (38,49,50) and wzxB mutations are deleterious in the presence of a fully functional O-antigen-producing machinery (51,52). We recreated both of these circumstances in the present study, and in both instances the accumulation of Und-PP-linked O-antigen intermediates induced morphological defects that were reversed by eliminating the production of O antigen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of WzxB causes the accumulation of Und-PPlinked O-antigen intermediates (49), which in turn limits the availability of Und-P for PG synthesis. Because of this, wzxB mutants are notoriously difficult to isolate (38,49,50) and wzxB mutations are deleterious in the presence of a fully functional O-antigen-producing machinery (51,52). We recreated both of these circumstances in the present study, and in both instances the accumulation of Und-PP-linked O-antigen intermediates induced morphological defects that were reversed by eliminating the production of O antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that wzxB flippase mutants acquire suppressing mutations that prevent the formation of O-antigen intermediates (38). Indeed, investigators who study WzxB function in Salmonella enterica do so in a genetic background where expression of O antigen is controlled by a galE mutation, which removes the first committed step in the biosynthetic pathway so that no Und-PP-linked O-antigen intermediates can accumulate until galactose is supplied (49,51,52). The deleterious effects of Und-P sequestration have also been noted for other transport mutants (53,54), as well as mutants that are unable to ligate O-antigen intermediates to the lipid A core (24) or that truncate the core oligosaccharide (55).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of the terminal DDH residue from several S. enterica Gal‐initiated O antigens results in poor Wzx translocation (Hong et al., ; Liu et al., , ). To assess this situation for the Y. pseudotuberculosis Wzx 1 and Wzx 2 , we made O:2a Δ abe (pPR2297) and O:1a Δ prt‐wbyH (pPR2326) constructs that both produce the same O unit main‐chain without a DDH residue, but express wzx 2 or wzx 1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However it has since been demonstrated on several occasions that Wzx can exhibit a strong preference for residues beyond the first sugar (Hong et al., ). Furthermore, inefficient Wzx translocation of nonpreferred O‐unit substrates results in cytoplasmic O‐unit accumulation and sequestration of UndP, which in turn interferes with peptidoglycan synthesis, causing a loss of membrane integrity and ultimately cell lysis (Jorgenson & Young, ; Liu, Stent, Hong, & Reeves, ). It is now becoming clear that Wzx substrate specificity represents a key checkpoint in the O‐antigen biosynthesis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that Wzx translocases can translocate only their native O units at optimal efficiency (Hong et al, 2012;Hong & Reeves, 2014;Liu et al, 2015). Wzy polymerizes the Und-PP-linked O units to produce long-chain O antigen, and also exhibits enormous sequence variation.…”
Section: Introductionmentioning
confidence: 99%